Sustainable Entrepreneurship Development Program for Dumagats: A Community Participatory Research - Pakig, Bebina Paglinawan (ASEAN Multidisciplinary Research Journal, 2022)
This research was conceptualized to identify an appropriate sustainable entrepreneurial development program for the Dumagats community in Sitio Ipo Barangay San Mateo, Norzagaray Bulacan. The program is recommended to capacitate and harness the skills and resources of the community to empower them as partners in economic development. This research aimed to develop, introduce, and help the community to pursue sustainable entrepreneurial activities to uplift them and elevate their daily living and self-growth. In the review of related literature and studies, it was revealed that entrepreneurship is a feasible pathway in helping to achieve and promote sustainable development in communities, especially those belonging to the marginalized sectors. Under the signed Executive Order No. 5, s. 2016, Filipinos’ ambitions for themselves and the country is considered essential to assist the government to outline and form programs, projects, and activities guiding towards the fulfillment of development results. Lundström’s and Stevenson’s “Motivation, Opportunity, and Skills model” (2013) was used primarily as a framework to identify how entrepreneurship can be promoted through different policy measures and to stimulate higher levels of entrepreneurial activity by influencing a greater supply of new entrepreneurs. This research utilized the convergent mixed methods design wherein, the interaction between the researcher and the participants consisted of a survey questionnaire distributed for the quantitative data gathering of the profile of the respondents. A consultative meeting was used as the main method of data collection to understand, explore, and determine the nature and factors related to subject matter and to help assist and understand the factors, problems, motivations, and interests from the perspective of the participants. This study participated by 94 Dumagat members in the community as per the recommended sample using the statistical tool, Slovin’s formula. The chieftain of the community selected the members of the Dumagats who participated in the study. Among the 11 Sitios where Dumagats are situated, Sitio Ipo was recommended by the National Commission on Indigenous People – Bulacan to participate in this study; the said area also has the highest population. The results of the study based merely on the quantitative data revealed that the respondents indeed part of the marginalized sectors of the society. Based on the results of the consultative meeting information data, the Dumagats have their own indigenous knowledge, system and procedures based on their way of living such as planting crops, catching fish, handcrafting, and sewing; however, lacking is improvement and introduction of new techniques. The most common problem encountered by the respondents are the lack of capital funds to continuously pursue their entrepreneurial plans and the lack of marketing linkages with a large market for contact to potential customers. Moreover, lack of qualified assistance or advice when it comes to entrepreneurial activities is also experienced. Nonetheless, the Dumagats community is motivated on any entrepreneurial activity despite their financial incapability. With these findings, it is recommended that the local government units and local development planners, provincial, municipal, local governments and private enterprises provide programs that will help improve and capacitate the skills of Dumagats community. The researcher formulated a one-year operational plan to give other avenues for a sustainable entrepreneurship development program proposal titled “I-Angat ang Dumagats 2021.” This is proposed to run from January 2021 to December 2021. This sustainable Entrepreneurial Development Program proposes to introduce, enhance, hone, and sustain the skills, capabilities, and motivation of the Dumagats community to pursue an entrepreneurial project or activity to help them uplift their lives and to achieve individual growth as perceived through their motivations to perform such activities.